Compartment syndrome of the forearm with life-threatening bleeding after fasciotomy as the presenting sign of postpartum acquired hemophilia A: a case report. Issue 3 (April 2019) - Van Laer, Marie; Penaloza, Andrea; Stockman, Willem; Meert, Philippe; Lambert, Catherine; Hermans, Cédric
Abstract : N/A: Acquired hemophilia A (AHA) is a rare bleeding disorder caused by the development of autoantibodies against clotting factor VIII. Although the cause of this disorder remains obscure, it is often linked to malignancies, drug administration, autoimmune diseases and pregnancy. In pregnancy-associated AHA, hemorrhagic symptoms usually present 1–4 months peripartum, however they may occur up to 1-year postpartum. Compartment syndrome of the forearm is also very uncommon complication of AHA but can have devastating consequences. We report a rare case of a compartment syndrome of the forearm in a 30-year-old woman 2.5 months postpartum as the presentation of pregnancy-associated AHA.